Optimizing Student Presentation Skills through Bluebooks - Wifda Muna Fatihia; Muhammad Abduh Amrie; Putri Faidah Khasanah (Yayasan Zia Salsabila, 2024)
Studies on student communication skills have been reviewed by many previous researchers from various scientific aspects. However, those that lead to the analysis of student presentation skills have not been studied and specifically, accompanied by media assistance such as Bluebooks. Furthermore, this research will describe efforts to optimize students' presentation skills through Bluebooks. This research is based on issue identification, issue analysis, and design of actualisation activities with the help of actuality, validity, problematics, and feasibility (APKL) analysis methods, urgency, seriousness, growth (USG) and fishbone diagram methods. The results of this study concluded that student presentation skills can be optimized with the help of Bluebooks, starting from the availability of modules, guides, videos of presentation materials, presentation tools and skills workshops, and intensive guidance on improving presentation skills for students periodically. Through this research, the implication is that the readiness of bluebooks-based media supports the readiness and presentation skills of students. Thus, learning is more conducive and discussion activities are more constructive-transformative in the classroom.